A qualitative study exploring the factors influencing admission to hospital from the emergency department. Issue 8 (29th August 2017) - Pope, Ian; Burn, Helen; Ismail, Sharif A; Harris, Tim; McCoy, David
Abstract : Objective: The number of emergency admissions to hospital in England and Wales has risen sharply in recent years and is a matter of concern to clinicians, policy makers and patients alike. However, the factors that influence this decision are poorly understood. We aimed to ascertain how non-clinical factors can affect hospital admission rates. Method: We conducted semistructured interviews with 21 participants from three acute hospital trusts. Participants included 11 emergency department (ED) doctors, 3 ED nurses, 3 managers and 4 inpatient doctors. A range of seniority was represented among these roles. Interview questions were developed from key themes identified in a theoretical framework developed by the authors to explain admission decision-making. Interviews were recorded, transcribed and analysed by two independent researchers using framework analysis. Findings: Departmental factors such as busyness, time of day and levels of senior support were identified as non-clinical influences on a decision to admit rather than discharge patients. The 4-hour waiting time target, while overall seen as positive, was described as influencing decisions around patient admission, independent of clinical need. Factors external to the hospital such as a patient's social support and community follow-up were universally considered powerful influences on admission. Lastly, the culture within the ED was described as having a strong influence (either negatively or positively) on the decision to admit patients. Conclusion: Multiple factors were identified which go some way to explaining marked variation in admission rates observed between different EDs. Many of these factors require further inquiry through quantitative research in order to understand their influence further.